1999
DOI: 10.1093/jnci/91.23.2020
|View full text |Cite
|
Sign up to set email alerts
|

Breast Tumor Characteristics as Predictors of Mammographic Detection: Comparison of Interval- and Screen-Detected Cancers

Abstract: Our data from a large group of women in a defined population indicate that screening mammography may miss tumors of lobular or mucinous histology and some rapidly proliferating, high-grade tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
197
10
7

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(241 citation statements)
references
References 37 publications
(47 reference statements)
27
197
10
7
Order By: Relevance
“…Two screening programmes were counted for Italy (see Material and Methods).-2 Percentages based on specified answers (missing values omitted) and for relevant programmes only.- 3 The European Guidelines (EG) defines an interval cancer as a primary breast cancer diagnosed in a woman who had a screening test with/without further assessment, which was negative for malignancy, either before the next invitation to screening or within a time period equal to a screening interval for a woman who has reached the upper age limit for screening. 6 -4 Missing data for the United States (see Material and Methods) and Canada.- 5 Missing data for the United States (see Material and Methods) and Denmark.- 6 Missing data for the United States (see Material and Methods), Denmark and Norway.- 7 Missing data for the United States (see Material and Methods); in New Zealand, data to be collected were in the process of being identified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two screening programmes were counted for Italy (see Material and Methods).-2 Percentages based on specified answers (missing values omitted) and for relevant programmes only.- 3 The European Guidelines (EG) defines an interval cancer as a primary breast cancer diagnosed in a woman who had a screening test with/without further assessment, which was negative for malignancy, either before the next invitation to screening or within a time period equal to a screening interval for a woman who has reached the upper age limit for screening. 6 -4 Missing data for the United States (see Material and Methods) and Canada.- 5 Missing data for the United States (see Material and Methods) and Denmark.- 6 Missing data for the United States (see Material and Methods), Denmark and Norway.- 7 Missing data for the United States (see Material and Methods); in New Zealand, data to be collected were in the process of being identified.…”
Section: Resultsmentioning
confidence: 99%
“…They occur because of the following: rapid tumour growth leads to cancers that truly develop in the interval after screening, cancers that are present are masked by characteristics of the breast or the cancer, readers miss subtle or minimal signs on the screening mammogram, or further assessment procedures fail to diagnose the cancer radiologically detected. 4,5 From a population-based perspective, IC are a key measure of the quality of the radiology performed and of the early impact of screening programmes. 6 A high incidence of IC adversely affects the ability of a screening programme to reduce mortality from breast cancer.…”
mentioning
confidence: 99%
“…Retrospective studies comparing interval and screen-detected cancers have shown that interval cancers are similar to cancers in unscreened women, and that screen-detected cancers generally have better prognostic indicators, with smaller tumours, fewer node-positive tumours, and a larger proportion of in situ tumours (Burrell et al, 1996;Porter et al, 1999). The current study confirms these observations, but of note is the similarity of the prognostic profile of interval cancers for those screened annually and that of interval cancers in those screened biennially, with the same being true for screen-detected cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that prognosis of the interval cancers may not differ from the clinically detected cases (Brekelmans et al 1995;Burrell et al, 1996) or it is intermediate to the screen detected and the clinically detected cancer groups (Groenendijk et al, 2003). Several studies have shown that interval cancers form a group of tumours with aggressive characteristics (Porter et al, 1999;Gilliland et al, 2000). Besides differences in stage, size and axillary lymph node status there are other biological differences between the screen-detected, interval and clinically detected cancers, which may influence the outcome of the patients.…”
Section: Discussionmentioning
confidence: 99%